(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the general composition (by economic occupation) and strata of the population during the Anushtegin dynasty, which played an important role in the history of the Uzbek nation and statehood. Very few historical sources of the Anushtegin dynasty provide information about the composition of the population. The work used source study, comparison with the period of previous dynasties, historical modeling in unknown aspects and other methods. During the Anushtegin dynasty, it was natural that the population consisted mainly of the ruler and his family. The studies show that the composition of the population during this period, according to their economic way of life, was divided into soldiers, farmers, artisans, traders and cattle breeders. They are collectively called “rayats”, and they can also be called “taxpayers to the treasury”. During this period, the strata of the population were determined by the rulers and the Sharia, thereby defining the roles and responsibilities of the general population in the state. For example, the presence of sayyids and scholars was encouraged as a symbol of the spiritual unity of the population, and elders were important persons in ensuring the participation of the population in the life of the state in a small unit. Judges, of course, belonged to important segments of the population as arbiters of Sharia and justice. Under the Anushtegin dynasty, the general composition of the population was determined by what they did and what their role was in the life of the state and society. We can say that these criteria have been observed throughout almost our entire history.